Strength reduction factors for S355 to S500 steel grades under steady-state and transient-state heating. (29th October 2019) - Hanus, Francois; Caillet, Nicolas; Gaillard, Sylvain; Vassart, Olivier
Abstract : Purpose: This paper aims to describe coupon tests performed at elevated temperatures on S355 to S500 steel grades and comparison of test results with previous research studies and current EN 1993-1-2 material laws. The objective is to state if these steel grades satisfy to the current material laws and if the scope of application of these laws could be extended to S500 grades. Design/methodology/approach: Two experimental programmes were launched to investigate the behaviour of S460M and S500M steel grades developed for hot-rolled sections. The first research programme was focussed on a comparison between S355 and S460 grades, where the second experimental programme was focussed on the recently developed S500M steel grade. The latter one comprised steady-state tests, transient-state tests and two large-scale beam tests. Findings: Results of steady-state and transient-state tests correlate well with the reduction factors defined in EN 1993-1-2, currently limited to S460 grade. On the basis of this study, the scope of EN 1993-1-2 applies to S500 grades. For steady-state tests, the testing procedure (with and without acceleration after Rp0, 2) led to noticeable differences. Transient-state tests, which are not standardised up to now, have been performed considering 5 K/min and 10 K/min constant heating rates. The slowest rate leads to lower strengths as creep effects are more significant. However, all the results are in line with EN 1993-1-2 material law. Importance should be given to the reference yield strength of steel at ambient temperature. Originality/value: The revision of EN 1993-1-2 is on-going and this piece of work provides a contribution for extending the scope of application of material law of steel under fire conditions.